Vertical muscle transposition with silicone band belting in VI nerve palsy - Dourado Leite, Ricardo (2016)
A woman aged 60 years developed a Millard-Gubler syndrome after a diagnosis of a cavernous angioma in the median and paramedian areas of the pons. In this context, she presented a right VI nerve palsy, right conjugate gaze palsy, facial palsy and left hemiparesis. To improve the complete VI nerve palsy, we planned a modified transposition approach, in which procedure we made a partial transposition of vertical rectus with a silicone band that was fixated posteriorly. After the procedure, the patient gained the ability to slightly abduct the right eye. We found no compensatory torticollis in the primary position of gaze. There was also an improvement of elevation and depression movements of the right eye. We obtained satisfactory results with a theoretically reversible technique, which is adjustable intraoperatively with no need of muscle detachment, preventing anterior segment ischaemia and allowing simultaneous recession of the medial rectus muscles, if necessary.